Vitrification of immature feline oocytes with a commercial kit for bovine embryo vitrification - Apparicio, M. [UNESP]; Ruggeri, E.; Luvoni, G. C. (Wiley, 2013)
The aim of this study was to evaluate the suitability of a commercial kit for bovine embryo vitrification for cryopreserving cat oocytes and to evaluate comparatively the effects of its use with slow freezing procedure on cryotolerance in terms of morphology and oocyte resumption of meiosis. Germinal vesicle stage oocytes isolated from cat ovaries were either vitrified (n=72) using a vitrification kit for bovine embryo or slow frozen (n=69) by exposing oocyte to ethylene glycol solution before being transferred to a programmable embryo freezer. After thawing and warming, oocytes were cultured for 48h and then were examined for meiosis resumption using bisbenzimide fluorescent staining (Hoechst 33342). Fresh immature oocytes (n=92) were used as the control group. The proportion of oocytes recovered in a morphologically normal state after thawing/warming was significantly higher in frozen oocytes (94.5%) than in the vitrified ones (75%, p<0.01). Morphological integrity after culture was similar in vitrified (73.6%) and slow frozen oocytes (76.8%); however, only 37.5% of the morphologically normal oocytes resumed meiosis after vitrification compared to 60.9% of those submitted to slow freezing procedure (p<0.01). Fresh oocytes showed higher morphological integrity (91.3%) and meiosis resumption rates (82.6%, p<0.002) than cryopreserved oocytes, irrespective of the procedure used. These results suggest that immature cat oocytes vitrified with a kit for bovine embryos retain their capacity to resume meiosis after warming and culture, albeit at lower rates than slow frozen oocytes. Vitrification and slow freezing methods show similar proportions of oocytes with normal morphology after culture, which demonstrate that thawed and warmed oocytes that resist to cryodamage have the same chances to maintain their integrity after 48h of culture. © 2012 Blackwell Verlag GmbH.
Keywords: animal; animal disease; cat; cattle; embryo culture; female; fertilization in vitro; in vitro oocyte maturation; male; morula; oocyte; physiology; prenatal development; vitrification; Animals; Cats; Cattle; Embryo Culture Techniques; Female; Fertilization in Vitro; In Vitro Oocyte Maturation Techniques; Male; Morula; Oocytes; Vitrification; Bovinae; Felidae